Increase in Antibiotic Utilisation in Primary Care Post COVID-19 Pandemic - Sky Wei Chee Koh; Si Hui Low; Jun Cong Goh; Li Yang Hsu (Antibiotics)
Introduction: The COVID-19 pandemic has disrupted antibiotic use; easing public health measures may alter infection presentations and antibiotic prescribing in primary care. The study investigated post-pandemic antibiotic utilisation trends in primary care. Methods: A multi-centre, retrospective cohort study was conducted across seven public primary care clinics in Western Singapore, which included all patients prescribed oral antibiotics between 2022 and 2023. Descriptive statistics were used to visualise the prevalence and conditions of the prescribed antibiotics. Antibiotic quality was evaluated using the WHO’s AWaRe (access, watch, reserve) classification. Antibiotic use was quantified using the number of items dispensed per 1000 inhabitants (NTI), defined daily doses (DDD) per 1000 inhabitants per day (DID), and DDD per 100 visits. Segmented regression analysis was applied to monthly prescriptions to assess the utilisation trends. Results: Antibiotic prescription rates increased significantly, from 3.5% in 2022 to 4.0% in 2023 (p = 0.001), with a 9.5% relative increase (38,920 prescriptions for 1,112,574 visits to 42,613 prescriptions for 1,063,646 visits). Respiratory conditions drove the increase in antibiotics use, with a 68.3% rise in prescriptions, with upper respiratory tract infections being the most common diagnosis for antibiotic prescriptions (n = 9296 prescriptions in 2023), with a steady monthly upward trend. Access group antibiotics accounted for >90% of prescriptions. The most antibiotics were prescribed for acne, with 36,304 DDD per 100 visits in 2023. Both NTI and DID significantly increased in 2022, largely contributed by a >100% increase in Watch group antibiotic use. Total antibiotic NTI dipped slightly in 2023, with a stable trend in both NTI and DID for all antibiotics. Conclusions: The post-COVID-19 pandemic surge in the antibiotic prescription rate for respiratory conditions and Watch group antibiotic use highlight the need for targeted stewardship interventions. Optimising acne treatment and diagnosis coding are key strategies to further reduce unnecessary prescriptions.